Proceedings of the Fourth International Conference on Lean Six Sigma for Higher Education 2017
DOI: 10.5703/1288284316371
|View full text |Cite
|
Sign up to set email alerts
|

A Continuous Improvement Journey in the Higher Education Sector: A Case Study of a University in Ireland

Abstract: Purpose: The paper's purpose is to contribute to a developing literature in relation to Continuous Improvement (CI), incorporating Lean Six Sigma (LSS) in Higher Education Institutions (HEIs). This paper follows on from a previous study which focused on the initial steps taken by an Irish university on its CI journey by discussing the next steps, detailing the findings from these. Design Methodology/Approach:A participative research approach is adopted. This is the second stage in a longitudinal study designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…At the heart of quality management in education is the continuous improvement [21]. A longitudinal study of an Irish university demonstrated the need for external reviews, internal expertise, as well as training and senior management commitment as key elements for the successful realization of continuous improvement in higher education institutions [7]. A recent improvement framework describes the ingredients for www.ijacsa.thesai.org transforming knowledge into practice to achieve sustainable change and improvement in education [5].…”
Section: Related Workmentioning
confidence: 99%
“…At the heart of quality management in education is the continuous improvement [21]. A longitudinal study of an Irish university demonstrated the need for external reviews, internal expertise, as well as training and senior management commitment as key elements for the successful realization of continuous improvement in higher education institutions [7]. A recent improvement framework describes the ingredients for www.ijacsa.thesai.org transforming knowledge into practice to achieve sustainable change and improvement in education [5].…”
Section: Related Workmentioning
confidence: 99%
“…Prasad explica que la aplicación de lean seis sigma con sus etapas DMAIC (Definir, medir, analizar, mejorar, controlar) garantiza la calidad de los servicios educativos, a través de la reducción de la variabilidad de sus procesos y del cambio cultural que se origina producto de una implementación continua de esta metodología [3]. Sin embargo, para alcanzar el éxito es necesario el compromiso de cada participante del sistema educativo [4].…”
Section: Iintroducciónunclassified
“…Waterbury 15 in her research highlighted the importance to understand the role of the senior leadership team when implementing Lean as a continuous improvement strategy. Reilly, Healy, Murphy, & O'Dubhghaill 16 defined key readiness factors which play role of "a pre-requisite to the successful implementation, deployment and sustainability of LSS in HEIs". These factors are "leadership and vision; management commitment and resources; linking Lean Six Sigma to University strategy; customer focus; and selecting the right people" (p.8).…”
Section: Lean Practices In Higher Education Institutions (Hei)mentioning
confidence: 99%